Исследование динамики C60 в газе - Мамонтов, Дмитрий Владимирович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
In the present work, we performed calculations of the molecular dynamics of fullerene in a volume filled with nitrogen. The temperatures of the gas component and fullerene were estimated, the ergodicity hypothesis was tested, and the velocity distribution of nitrogen molecules was obtained, corresponding to the theoretical Maxwell distribution.